(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was conducted to assess the effect of dietary Moringa oleifera leaf (MOL) feed supplementation on serum biochemical parameters of broilers challenged with very virulent infectious bursal disease virus (vvIBDV). Materials and methods: Two hundred and forty day-old Ross 308 hybrid broiler chicks were randomly assigned into four groups (A, B, C and D) of 60 chicks each and raised in deep litter housing. Broiler starter (BS) and broiler finisher (BF) mash were formulated each with 5% MOL included as part of the feed ingredient for broilers in groups A and B while BS and BF for broilers in groups C and D were formulated without MOL. Broilers in groups A, B and C were challenged intraocularly at 35 days of age with with 0.05 mL of a live vvIBDV, while those in group D served as control. Blood was collected from 10 broilers in each group via the wing vein at 35, 38 and 42 days of age to determine their serum biochemical profile. Results: The level of melondialdehyde (MDA) was observed to significantly decrease in groups A and C. There was a significant decrease in the level of AST in group A, B, C and D. The values of ALT significantly decreased in group A, B, C and D. Conclusion: Supplementing broilers feed with MOL neither protect the liver from damage nor prevent lipid peroxidation. http://doi.org/10.5455/javar.2018.e260